2007
DOI: 10.1093/ndt/gfm784
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effect of the natural antioxidant hydroxytyrosol on cyclosporine nephrotoxicity in rats

Abstract: The reported data indicate that effective DOPET protection from CsA-induced oxidative stress is associated with a mild effect on histological damages and does not affect the altered glomerular function and the hypertension, thus indicating that kidney injury by CsA is only in part dependent on oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 36 publications
4
35
1
Order By: Relevance
“…Several previous studies had suggested that cyclosporine nephrotoxicity may be improved or prevented by antioxidants. [12][13][14][15][16][17] A meta-analysis of clinical trials of CoQ10 for hypertension concluded that CoQ10 had potential for lowering blood pressure in hypertensive patients 18 ; however, in this study, no significant reduction of systolic blood pressure was observed when rCoQ10 was administered with cyclosporine. A possible explanation for this finding is that cyclosporine-induced hypertension may be caused by activation of the intrarenal renin-angiotensin axis, 7 but the renal protective effect of rCoQ10 may be accomplished by another mechanism.…”
Section: Discussioncontrasting
confidence: 60%
“…Several previous studies had suggested that cyclosporine nephrotoxicity may be improved or prevented by antioxidants. [12][13][14][15][16][17] A meta-analysis of clinical trials of CoQ10 for hypertension concluded that CoQ10 had potential for lowering blood pressure in hypertensive patients 18 ; however, in this study, no significant reduction of systolic blood pressure was observed when rCoQ10 was administered with cyclosporine. A possible explanation for this finding is that cyclosporine-induced hypertension may be caused by activation of the intrarenal renin-angiotensin axis, 7 but the renal protective effect of rCoQ10 may be accomplished by another mechanism.…”
Section: Discussioncontrasting
confidence: 60%
“…RCoQ10 also diminished TGF-beta expression in the proximal renal tubular cells. There are several animal and clinical studies suggesting that antioxidative agents have some preventive effect of CyA nephrotoxicity (7)(8)(9)(10)(11)(12). In 2004, Dlugosz et al reported the benefit of CoQ10 on renal transplant recipients for the first time (13); however, they used ubiquinone, the oxidized form of CoQ10.…”
Section: Discussionmentioning
confidence: 99%
“…For tubular injury, the following score was used: 0 ¼ no tubular injury; 1 ¼ <25% of tubules injured; 2 ¼ from 25 to 50% of tubules injured; 3 ¼ from 51 to 75% of tubules injured; 4 ¼ more than 76% of tubules injured. 19 Measurements of Renal MDA Levels, SOD, ACE, Ang II, and NADPH Oxidase Activities…”
Section: Renal Histopathological Examinationmentioning
confidence: 99%